1997
DOI: 10.1007/s003359900529
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of maternal transmission ratio distortion at Om and direct evidence that the maternal and paternal “DDK syndrome” genes are linked

Abstract: The polar, preimplantation-embryo lethal phenotype known as the "DDK syndrome" in the mouse is the result of the complex interaction of genetic factors and a parental-origin effect. We previously observed a modest degree of transmission-ratio distortion in favor of the inheritance of DDK alleles in the Ovum mutant (Om) region of Chromosome (Chr) 11, among offspring of reciprocal F1-hybrid females and C57BL/6 males. In this study, we confirm that a significant excess of offspring inherit DDK alleles from F1 mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The phenotypic effect of the Om locus is on embryonic survival and allelic frequencies of offspring; the extent of its effect is cross-dependent, and evidence has suggested that it may be genomically imprinted, hypothesized to normally express only the maternal allele (Sapienza et al 1992;Babinet et al 1990;de Villena et al 1997). Allelic inheritance at Alcp2, whose maximum likelihood position is nearly identical to the position of Om (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The phenotypic effect of the Om locus is on embryonic survival and allelic frequencies of offspring; the extent of its effect is cross-dependent, and evidence has suggested that it may be genomically imprinted, hypothesized to normally express only the maternal allele (Sapienza et al 1992;Babinet et al 1990;de Villena et al 1997). Allelic inheritance at Alcp2, whose maximum likelihood position is nearly identical to the position of Om (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Om locus is associated with the “DDK syndrome” (dysdiadochokinesia), named after a strain for which mating DDK females with males of other genetic backgrounds results in litters exhibiting over 95% embryonic lethality [ 34 ]. The region on chromosome 11 carrying the Om allele segregates with transmission bias in female meiosis [ 35 , 36 ] during the second meiotic division only [ 2 , 37 ]. Curiously, loci flanking the Om locus also segregate with a transmission bias, albeit with lower efficiency [ 35 , 36 ].…”
Section: Transmission Biases Reported In Micementioning
confidence: 99%
“…The region on chromosome 11 carrying the Om allele segregates with transmission bias in female meiosis [ 35 , 36 ] during the second meiotic division only [ 2 , 37 ]. Curiously, loci flanking the Om locus also segregate with a transmission bias, albeit with lower efficiency [ 35 , 36 ].…”
Section: Transmission Biases Reported In Micementioning
confidence: 99%
“…In such cases, polymorphic markers within the regions in question were typed for the majority of the BxD strains. Polymerase chain reaction (PCR) was performed as described by Pardo-Manuel de Villena et al (1997). Primers were obtained from Research Genetics, Inc.…”
Section: Genotype Analysis By Polymerase Chain Reactionmentioning
confidence: 99%
“…DDK egg RNA can likewise lead to an embryonic lethal phenotype when injected into non-DDK eggs or blastomeres, indicating that the maternal factor is present within the egg as an RNA (Renard et al, 1994). The locus responsible for the DDK phenotype has been mapped to mouse chromosome 11 (Baldacci et al, 1992;Sapienza et al, 1992), and more recent studies indicate that the gene encoding the maternal factor and a paternal responding gene reside at the same locus, or two closely linked loci (Pardo-Manuel de Villena et al, 1997).…”
mentioning
confidence: 99%